2020
DOI: 10.1111/cup.13830
|View full text |Cite
|
Sign up to set email alerts
|

Perniosis during the COVID‐19 pandemic: Negative anti‐SARS‐CoV‐2 immunohistochemistry in six patients and comparison to perniosis before the emergence of SARS‐CoV‐2

Abstract: Background: Acral inflammatory lesions that have some resemblance to idiopathic or autoimmune-associated perniosis (chilblains) have been described in multiple countries during the COVID-19 pandemic. Methods: We examined histopathologic findings in six consecutive such cases from five patients received in mid-May to mid-June of 2020, evaluating immunohistochemical staining for the SARS-CoV-2 nucleocapsid protein. We compared these six cases to eight cases diagnosed as perniosis between January and June of 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 29 publications
0
37
0
1
Order By: Relevance
“…Livedo reticularis-like lesions are frequently mild, transient and not associated with thromboembolic complications [68, 69]. On the contrary, livedo racemosa-like lesions and retiform purpura have often been described in patients with severe coagulopathy [60-72].…”
Section: Livedo Reticularis/racemosa-like Patternmentioning
confidence: 99%
“…Livedo reticularis-like lesions are frequently mild, transient and not associated with thromboembolic complications [68, 69]. On the contrary, livedo racemosa-like lesions and retiform purpura have often been described in patients with severe coagulopathy [60-72].…”
Section: Livedo Reticularis/racemosa-like Patternmentioning
confidence: 99%
“…-Some authors have also shown positive anti-SARS-CoV/SARS-CoV-2 immunostaining on skin biopsy specimens of chilblains, which seem to confirm the presence of the virus in the lesions (Colmenero et al, 2020;Santonja et al, 2020). However, due to lack of specificity, these immunostainings should be interpreted with caution (Baeck et al, 2020b;Ko et al, 2020). -Conversely, RT-PCR and anti-SARS-CoV-2 serology were mostly negative (Baeck et al, 2020c;Caselli et al, 2020;Colonna et al, 2020;Denina et al, 2020;El Hachem et al, 2020;Freeman et al, 2020b;Garcia-Lara et al, 2020;García-Legaz Martínez et al, 2020;Le Cleach et al, 2020;Lesort et al, 2020;Mahieu et al, 2020;Neri et al, 2020;Rizzoli et al, 2020;Roca-Ginés et al, 2020;Rouanet et al, 2020;Stavert et al, 2020).…”
mentioning
confidence: 99%
“…Clustering of true IP in children consequent to lifestyle changes during the lockdown has also been reported 5 . Histopathological characteristics of CLL have been described in limited studies and appear indistinguishable from IP 3,6‐12 . We at our tertiary care center in Dehradun (Uttarakhand) saw clustering of cases of IP from November 2019 till February 2020.…”
Section: Introductionmentioning
confidence: 74%
“…Keratinocyte necrosis was seen in a higher number of patients with IP (50%) as compared of CLL (22.2%–42.8%). Basal vacuolar damage has been reported in variable proportions in CLL ranging from 14.3% to 100% 6‐11 . However, in a large histopathological series of 18 CLL cases, it was seen in 77.7% 3 .…”
Section: Discussionmentioning
confidence: 98%